Exploring Multiple Sclerosis (MS) and Amyotrophic Lateral Scler osis (ALS) as Neurodegenerative Diseases and their Treatments: A Review Study - Deeb, Omar; Nabulsi, Maisa (Current Topics in Medicinal Chemistry, 2020)
Growing concern about neurodegenerative diseases is becoming a global issue. It is estimated that not only will their prevalence increase but also morbidity and health burden will be concerning. Scientists, researchers and clinicians share the responsibility of raising the awareness and knowledge about the restricting and handicapping health restrains related to these diseases. Multiple Sclerosis (MS), as one of the prevalent autoimmune diseases, is characterized by abnormal regulation of the immune system that periodically attacks parts of the nervous system; brain and spinal cord. Symptoms and impairments include weakness, numbness, visual problems, tingling pain that are quietly variable among patients. Amyotrophic Lateral Sclerosis (ALS) is another neurodegenerative disease that is characterized by the degeneration of motor neurons in the brain and spinal cord. Unlike MS, symptoms begin with muscle weakness and progress to affect speech, swallowing and finally breathing. Despite the major differences between MS and ALS, misdiagnosis is still influencing disease prognosis and patient’s quality of life. Diagnosis depends on obtaining a careful history and neurological examination as well as the use of Magnetic Resonance Imaging (MRI), which are considered challenging and depend on the current disease status in individuals. Fortunately, a myriad of treatments is available now for MS. Most of the cases are steroid responsive. Disease modifying therapy is amongst the most important set of treatments. In ALS, few medications that slow down disease progression are present. The aim of this paper is to summarize what has been globally known and practiced about MS and ALS, as they are currently classified as important growing key players among autoimmune diseases. In terms of treatments, it is concluded that special efforts and input should be directed towards repurposing of older drugs and on stem cells trials. As for ALS, it is highlighted that supportive measurements and supplementary treatments remain essentially needed for ALS patients and their families. On the other hand, it is noteworthy to clarify that the patient-doctor communication is relatively a cornerstone in selecting the best treatment for each MS patient.
Keywords: Neurodegeneration